Raymond Williams : literature, Marxism and cultural materialism - Higgins, John Anthony (Department of English Language and Literature, 2017)
The guiding principle of this study is that Williams's engagement with English studies cannot be understood in terms purely internal to the discipline of English. As well as writing against the official culture of liberal and conservative literary studies, Williams also wrote in opposition to what he read as the orthodoxies of Marxist thinking on literature, culture and politics. Arguing first against Marxist literary criticism as he knew it from the 1930s, he maintained an ever sceptical and ever critical stance towards the later trends of Althusserian and poststructuralist theory, while at the same time continuing his always defining commitment to socialist politics. While the terms of this larger argument are necessarily present throughout, Chapter Five focuses on them more narrowly, and traces their development in Williams' thinking from the late 1950s through to the development of the concept of cultural materialism in Marxism and Literature in 1977.